Inclusão de pessoas com deficiência visual na escola regular: bases organizativas e pedagógicas no Estado do Acre - Maria de Lourdes Esteves Bezerra (2011)
This work studies the inclusion of visually impaired people, from the mid-1990s to the current days, in four state schools in the city of Rio Branco - Acre, because it was the moment when the main political and educational providences were taken by the public system authorities in order to turn the inclusion an effective practice. Based on this, its objective moves towards the analysis of pedagogical practices of these institutions in order to identify their teaching model and the concrete manners to organize and manage such classes, intended to educate in the diversity and to the diversity. It is an empyrical qualitative research, which methodology is characterized by the study of multiple cases, and the main subjects of the investigation are teachers, schools managers, teaching staff, blind or low vision students, who work and/or study in these four schools. The study reveals several aspects how this process has been developing, its organizational and pedagogical bases, the comprehension of different educational instances and its subjects concerning the inclusion, its searches to adjust to this educational model, and to adequately answer to all students' educational necessities, under the logics of diversity and heterogeneity. Considering that inclusion is a multifaceted process, it is necessary to ground the research in different areas which carry the investigation about this theme, such as Philosophy and Sociology of Education, for instance, underpinned by the works of Bueno, Carlos Skliar, Mendes, Santos, etc. Besides this, from the field of Psychology of Education, Special Education, Education and Teacher Education, contributions from several Brazilian scholars, namely Carvalho, Freitas, Kassar, Lima, Montoan, Masini, among others; and from foreign thinkers highlighting César Coll, Cortesão, González, Magalhães and Stoer, Nóvoa, Stainback and Stainback, and many others, who helped in the understanding of aspects, such as: the role of the school as a place for inclusion, the issues relating to the differences, equality, diversity, and the visual impairment. And finally, this study shows that inclusion is a complex and polemic process, and for this very reason, it needs to be more discussed and understood by all people involved in its planning, execution, and follow-up actions, because it has already been studied for some time, much still needs to be realized. In this perspective, teacher education, initial and continued, is shown as one of the essential points so that the inclusion of visually impaired students in the schools, particularly in this research, and of other students presenting other kinds of impairments, or without any difficulty, reach the wished success, and considering that the inclusive school appears to be the new educational, didactical, curricular, organizational and institutional place, and therefore it demands that the development of proper attitudes arise from its reflexive professionals.